Meneropong Morfologi Kota Pekanbaru pada Era Kolonial Belanda (1919-1942) - Sabrina Sabrina; Zulqaiyyim Zulqaiyyim (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2023)
This study discusses the morphology changes of Pekanbaru City during the two decades of the Dutch colonial era (1919-1942). This study had used historical research methods with a city morphology perspective. The stages had been heuristics, source criticism, interpretation, and historiography. During that time, Pekanbaru had been developed by the Dutch Colonial Government as an administrative center and trading center. In order to develop that function, the Dutch Colonial Government had built a rubber plantation as a trading commodity at the Pekanbaru Port, which was on the banks of the Siak River. They had also built infrastructure, educational, medical, recreation facilities, etc., so that this city had become attractive to urbanites, resulting in an increase in population. Therefore, a new area of the city had been built to the south so that a morphological transformation had occurred in that city. Thus, in 1919-1942, Pekanbaru had become the administrative center and trade center to support the surrounding plantations.